Picking interstitial lung disease out of the myositis haystack - Jennifer Hannah; Harsha Gunawardena (Indian Journal of Rheumatology)
Interstitial lung disease (ILD) is a common manifestation of the connective tissue disease (CTD) associated idiopathic inflammatory myopathies (IIM). Although patients may be diagnosed as having polymyositis (PM) or dermatomyositis (DM) under the IIM spectrum, it is quite clear that risk, pattern of ILD and disease course between subgroups of patients is different. The natural history may be asymptomatic and slowly progressive or stable, chronically progressive or fulminant rapidly progressive depending on ILD subtype. ILD can be the initial presenting feature and this can make recognition of an underlying CTD-IIM overlap more difficult with some patients initially misdiagnosed with idiopathic pulmonary fibrosis. Therefore, early recognition and characterization of patients can influence management and prognosis. It is clear than certain clinical and serological features phenotype patients into more specific CTD-IIM ILD subgroups. A number of myositis-CTD overlap associated antibodies and their clinical patterns have been described over the last few years. The hallmark CTD-IIM ILD subgroup is antisynthetase syndrome, characterized by autoantibodies to tRNA synthetases. Muscle weakness is not universally present and parenchymal lung disease can predominate. Anti-MDA5 DM has a distinct cutaneous pulmonary phenotype and is significantly associated with the development of ILD with different patterns seen in different ethnic groups. Other autoantibodies associated with ILD include those targeting nucleolar autoantigens such as anti-PM-SCL, again with characteristic syndromes. Picking ILD out of the “myositis haystack” can be complex. This heterogeneous disease group requires robust multidisciplinary collaboration between rheumatologists, pulmonologists, thoracic radiologists, and histopathologists to bring together clinical assessment to reach a diagnostic conclusion so optimal outcomes can be achieved.